The Effect of Dialectic Behavioral Counseling on Depression, Anxiety, and Postpartum Hematocrit Level - Amiri, Nasrin Pour; Ahmadi, Atefeh; Mirzaee, Firoozeh; Mirzai, Moghadameh; Shahrokhi, Nader (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2021)
Objective Childbirth is a biological, psychological, and sociological event that can be a positive or negative experience, and, without support, this period may be potentially damaging. Parturition may distort maternal emotions and lead to short- or long-term disorders such as postpartum depression and anxiety. The present research aims to study the effects of dialectic behavioral therapy-based counseling on depression, anxiety symptoms, and postpartum hematocrit level.Methods The current research is a clinical trial study, and the sample was selected using parturients who were referred to the Health General Center with a diagnosis of postpartum depression and anxiety. The sample size consisted of 116 subjects who agreed to participate in the study. The patients in intervention group underwent group dialectic behavioral counseling (10 sessions/one session per week) and the control group did not receive any type of intervention. The patients were assessed in the first and last sessions as well as 2 months after the end of the sessions, using the Beck depression scale and Spielberg anxiety scale as well as the results of hematocrit tests. Data were analyzed using the IBM SPSS Statistics for Windows, Version 21.0 (IBM Corp., Armonk, NY, USA)Results The results implied the effectiveness of dialectic behavioral therapy on reduction of the depression score, anxiety symptoms (p-value ≤ 0.0001), and hematocrit level (p-value = 0.04). The participants' depression, anxiety, and hematocrit levels decreased in the experiment group compared to the control group, and this decrease has remained until the 2-month follow-up.Conclusion It seems that dialectic behavioral counseling reduces the levels of postpartum depression, anxiety, and hematocrits.
Keywords: postpartum depression; postpartum anxiety; hematocrit; dialectic behavioral therapy